Father, Son, and Constitution : How Justice Tom Clark and Attorney General Ramsey Clark Shaped American Democracy - Wohl, Alexander (Book collections on Project MUSE., 2013)
A dual career biography of Tom and Ramsey Clark and their profound impact on American law and society. For nearly three quarters of a century, they influenced presidents, policies, and legal rulings, during careers that tracked closely with some of the most significant and controversial episodes in American history.